Morphology, wettability and osseointegration of dental implant surfaces: a systematic review. - Silva Canto, Mauro; Cunha Melo, Amanda (Brazilian Journal of Implantology and Health Sciences, 2020)
The objective of this study was to perform a systematic review on the effects of morphology and wettability of surfaces on the osseointegration of dental implants. A bibliographic search of articles published in the last tem years was conducted on PubMed database. The following search terms were applied to select the most relevant studies: “wettability” OR “surface energy” OR “BIC” OR “hydrophilic” AND “dental implants”. Several modifications of implant surfaces resulted in na increase of hidropholicty and wetabllity for the osseointegration process. The morfologic aspects at micro- and nano-scale of the implant surfaces can promote the wetabillity and therefore to stimulate platelets and osteogenic cells. Nowadays, the enhancement of topography and hidrophilicity of implant surfaces are key factor to accelerate the osseointegration process.